More Than Bodies: Diné Masculinities in Anticolonial Spaces and Embodied Discursive Action - J. Jeffery Clark (Journal of Global Indigeneity)
The article presents interviews with two Diné men, where they describe how they enact and model masculine identities in their anticolonial community organising. The discussions centre on being a cis-hetero Diné man, kinship roles and responsibilities, Diné masculinity and femininity, and what it means to create healthy masculinity as an anticolonial practice. The article shows how they imagine, enact, and model their masculinity to contest colonial technologies that disavow Diné men of their body, kin, and land. And through the anticolonial Diné masculinity they live out, they demonstrate what embodied discursive action looks like in their work and communities. Their masculinity offers hope for a future beyond settler domination where Diné men are once again decorated with possibilities, love, care, and health.